ANALISIS PENGARUH KEPUASAN PELANGGAN TERHADAP KEPERCAYAAN DAN LOYALITAS PELANGGAN UNTUK MENINGKATKAN MINAT BELI ULANG (STUDI PADA ONLINE STORE LAZADA.CO.ID) - Norhermaya, Yashinta Asteria; Soesanto, Harry (Diponegoro Journal of Management, 2016)
This study aims to determine the effect of customer satisfaction perceivedby Lazada.co.id customers to the establishment of trust and customer loyalty to the repurchase intention. The population in this study is Lazada.co.id customer who have made purchase more than 3 times. This study use a Structural Equation Models whit non probability sampling and maximum likehood analysis method by using AMOS 2.2. The result of this study indicate that customer satisfaction has the greatest influence on trust. In addition, the trust and customer loyalty also have a positive influence to the repurchase intention